A Framework for Categorizing Chronically Problematic Sexual Behavior. Issue 4 (2nd October 2017) - Herring, Bill
ABSTRACT: This article introduces a framework for categorizing chronically problematic sexual behavior. It identifies patterns of commitment violations, values conflicts, diminished self-control, negative consequences, and lack of sexual responsibility as independent categories of chronically problematic sexual behavior. It recognizes that many forms of problematic sexual behavior can be reduced or eliminated by changing either sexual or nonsexual components of a person's life. This framework does not use the type or frequency of sexual behavior as an assessment variable. It neither postulates causes of problematic sexual behavior nor offers techniques for its reduction or elimination. This framework does not replace any existing theories or assistance models. Since it is capable of supporting theories representing many different perspectives, it expands the potential for interdisciplinary collaboration to widen the range of options available to more people who want to reduce or eliminate chronically problematic aspects of their sexual behavior.